The Application of Chomsky’s Syntactic Theory in Translation Study - Wu, Ying; Xu, Runjiang (Journal of language teaching and research, 2011)
Since he put forward his Transformational- generative Grammar (TG), many scholars have tried to use the concepts of deep structure (D-structure) and surface structure (S-structure) to provide a theoretical basis for translation studies. Linguistics is where they have paid most attention as both linguistics and translations are the study of language. [...]as soon as Chomsky's TG theory came into being, scholars have been interested in applying this theory to the scientific research of translation. [...]this example is enough to illustrate that syntactic analysis alone is not enough to determine the sentence meaning. [...]it's cannot act as the only information source of translation. According to TG theory, it is clear that ST1 and ST2 have different deep structures because they have different syntactic relationships. [...]according to Nida's theory, they should have different deep structures in Chinese respectively, and TT1 is undoubtedly a correct translation of ST1 and TT2 of ST2.